2020
DOI: 10.3390/ijms21082783
|View full text |Cite
|
Sign up to set email alerts
|

A Tetra-Panel of Serum Circulating miRNAs for the Diagnosis of the Four Most Prevalent Tumor Types

Abstract: The purpose of this study is to clinically validate a series of circulating miRNAs that distinguish between the 4 most prevalent tumor types (lung cancer (LC); breast cancer (BC); colorectal cancer (CRC); and prostate cancer (PCa)) and healthy donors (HDs). A total of 18 miRNAs and 3 housekeeping miRNA genes were evaluated by qRT-PCR on RNA extracted from serum of cancer patients, 44 LC, 45 BC, 27 CRC, and 40 PCa, and on 45 HDs. The cancer detection performance of the miRNA expression levels was evaluated by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Recently, Pastor-Navarro and García-Flores et al proposed using a panel of four miRNAs for serum PCa diagnosis, including miR-375-3p, miR-182-5p, and miR-21-5p [ 35 ]. They showed that these miRNAs have great potential for PCa diagnostics, regarding their AUC values [ 35 ]. Again, our findings encourage these conclusions, showing that miR-182-5p and miR-375-3p deserve and require focus in further research.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pastor-Navarro and García-Flores et al proposed using a panel of four miRNAs for serum PCa diagnosis, including miR-375-3p, miR-182-5p, and miR-21-5p [ 35 ]. They showed that these miRNAs have great potential for PCa diagnostics, regarding their AUC values [ 35 ]. Again, our findings encourage these conclusions, showing that miR-182-5p and miR-375-3p deserve and require focus in further research.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, many dysregulated miRNAs were found, but most of them were not consistently analysed in more than one study. MiR-21 was the most-reported microRNA over the included studies, with 16 studies ([ 14 , 17 , 19 , 21 , 29 , 36 , 37 , 38 , 41 , 44 , 45 , 50 , 51 , 55 ], followed by miR-31([ 14 , 31 , 50 ]), miR-15b ([ 14 , 36 , 53 ]), and miR-20a ([ 15 , 39 , 48 ]), which were used in three studies each. However, in these studies, the expression of miR-20a did not have coherent values.…”
Section: Resultsmentioning
confidence: 99%
“…The pretreatment method was slightly modified on the basis of the existing literature. 37–39 2.5 mL of serum was taken and incubated at 95 °C for 15 min, cooled on ice for 3 min, centrifuged at 17 000× g at 4 °C for 15 min, and MNPs-cDNA was added to the supernatant for capture and enrichment of miR-21 (the final volume was 200 μL, the concentration of miR-21 was concentrated by 12.5 times). The established method was used to detect and calculate the concentration of miR-21 in the original serum.…”
Section: Experimental Methodsmentioning
confidence: 99%